2022
DOI: 10.1155/2022/9889127
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane Bagasse as the Source of Nanocrystalline Cellulose for Gelatin-Free Capsule Shell

Abstract: Gelatin-free capsules are possibly produced through an innovation which involves utilizing environmentally friendly materials derived from plants such as bagasse which are produced into nanocrystalline cellulose (NCC). This research was conducted to report the extraction and characterization of NCC from the abundant industrial plantation waste of sugarcane and its application as the base material for gelatin-free capsule shell material. The process involved using different concentrations of NCC at 1%, 2%, 4%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…These results were obtained after the preparation of raw materials, the cooking process, and bleaching. The cooking and bleaching process increased the efficiency of mechanical defibrillation in the extraction process of nonfibrillated cellulose, which was based on removing impurities and destroying the cell wall structure [ 25 ]. The results of the analysis of COPEFB fiber (biofiber) mechanically and retting without chemicals contain a chemical composition of alpha cellulose 46.62 ± 0.11%, lignin 23.17 ± 0.38%, ash content 3.35 ± 0.01%, and extractive 7.60 ± 0.17%.…”
Section: Resultsmentioning
confidence: 99%
“…These results were obtained after the preparation of raw materials, the cooking process, and bleaching. The cooking and bleaching process increased the efficiency of mechanical defibrillation in the extraction process of nonfibrillated cellulose, which was based on removing impurities and destroying the cell wall structure [ 25 ]. The results of the analysis of COPEFB fiber (biofiber) mechanically and retting without chemicals contain a chemical composition of alpha cellulose 46.62 ± 0.11%, lignin 23.17 ± 0.38%, ash content 3.35 ± 0.01%, and extractive 7.60 ± 0.17%.…”
Section: Resultsmentioning
confidence: 99%
“…The morphological observation results showed that RVF from WEFB biomass had a larger diameter than SEFB with values of 17.00 mm and 16.5 mm, respectively ( Figure 9 ). In addition, SEM micrographs show the surface morphology of WEFB fibers consisting of bundles of microfibrils with deposited cellulose components such as wax, lignin and hemicellulose [ 38 , 39 , 40 ]. The aggregation of micro crystals observed is presumably due to the water evaporation step during sample preparation.…”
Section: Resultsmentioning
confidence: 99%
“…The results show that this method extracts SiO 2 with reduced impurity content compared to other methods (Palupi et al, 2019a;Palupi et al, 2019b). The purity value reaches 85.41% at a combustion temperature of 800 o C. It turns out that by modifying the system, the effects of contaminants can be mitigated (Sabara et al, 2022b). However, the calculated purity value is lower than the previous method; therefore, further studies are still needed.…”
Section: Introductionmentioning
confidence: 87%
“…By employing this method (Nandiyanto et al, 2016), SiO 2 of purity of 68% can be extracted from rice straw. Several studies reported the extraction of SiO 2 by adopting a simpler method consisting of combustion of biomass (forming charcoal) (Sabara et al, 2022b), leaching (using acid), and ashing (Rohaeti et al, 2010;Aminullah et al, 2015;Adli, 2018). This method has been used to extract SiO 2 from rice husk biomass, with a purity of 99% (Sintha, 2017;Irzaman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%